Multi-Logistic Regression Binary Response’ Technique to determine the Problems that most affect Bullying on Students with Intellectual Disabilities from the Parents’ Perspective - Alqahtani, Dr. Ali (International Journal of Psychosocial Rehabilitation, 2020)
The research aimed to determine the factors affecting the increase in bullying phenomenon on students with intellectual disabilities from the perspective of parents in the Kingdom of Saudi Arabia. The sample consisted of (72) parents of primary and middle school students who suffer from intellectual disabilities in Asir region. A questionnaire was developed to determine the most influential problems in bullying on students with intellectual disabilities, consisting of nine phrases and all of them of binary type, and the following statistical analyzes were used (Maximum de vraisemblance -Wald-Hosmar and Lemshow-Goodness of fit). The results of the research indicated that half of the independent variables represented by (the intellectually disabled being exposed to cases of bullying inside the school, electronic bullying and the role of domestic violence and the role of electronic games practiced by peers) had a significant impact and importance in increasing bullying cases of students with intellectual disabilities in Asir region from the perspective of their parents.